IMPROVING ENERGY EFFICIENCY STRATEGY IN RESIDENTIAL BUILDINGS - Vrusho, Boriana; Golgota, Alma; Dhoska, Klodian; Abotaleb, Mostafa (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2025)
Reducing the energy demand of residential buildings is crucial for mitigating climate change, lowering energy costs, reducing health risks associated with fuel poverty, and improving the overall residential environment. Given the global significance of these challenges, this research aims to explore the impact of energy-saving measures in residential buildings, focusing on façade renovation systems in Tirana, Albania. The methodology employed in this research work involved a comprehensive approach combining field assessments, energy performance analysis of completed projects, and case studies of residential buildings in Tirana. The research specifically focused on the implementation of façade renovation systems and evaluated their impact on reducing energy consumption. The results demonstrate significant improvements in energy performance following the renovation of building façades. Enhanced insulation, upgraded materials, and the addition of energy-efficient windows led to reduced heating and cooling demands, contributing to a more stable indoor climate and lower energy consumption. The energy simulations confirmed that facade renovations resulted in a notable reduction in overall energy use, particularly during the colder months. The findings suggest that facade renovation systems are an effective strategy for reducing the energy demand of residential buildings in Tirana. These improvements not only help to mitigate the effects of climate change by lowering carbon emissions but also offer a cost-effective solution for improving the quality of life for residents. This study offers a novel contribution by focusing specifically on the impact of facade renovation systems in the context of residential buildings an area with limited previous research on energy efficiency improvements.